Embedding randomised controlled trials in renal registries - Caskey, Fergus J; Jardine, Thabiet; Davids, M Razeen (African Journal of Nephrology, 2019)
Traditional randomised controlled trials that rely on research staff to collect data are becoming increasingly expensive. As a result, the number of interventions that can be scrutinised for effectiveness will be limited. Further, while results from such trials have high internal validity, they will have limited external validity – generalisability to the real-world population. One solution is to adopt a more pragmatic approach and embed randomisation into routine healthcare databases such as registries. There are a number of ways that this can be done. Most commonly, registries simply provide extended follow-up to traditional explanatory trials, but with the necessary permissions more novel approaches are possible. Registries can be used to identify potentially eligible participants, provide the baseline data and provide all of the follow-up data. Proportionate to the risk associated with the intervention, routine healthcare databases can also provide some of the safety monitoring data, greatly reducing the burden and cost of the trial. To illustrate the opportunities and challenges, a number of reported and ongoing registry trials are presented.